Bilingual Digital Eduliteracy for Marketing Management of Small and Medium Enterprises Centers in Ilomata Village, Bilato District - Haris Danial; Sri Widyarti Ali; Indri Wirahmi Bay (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The importance of the existence of UMKM is able to support the surrounding economy and be able to revive other supporting local businesses. This community service aims to: 1) There is a need for community provision and understanding of the concept of digital-based marketing as a support for business activities in the village, 2) Facilitate access to village sales and production processes so that community businesses can run smoothly, 3) There is a need for bilingual digital eduliteration to the community as an effort in marketing in the village. This community service includes five stages including the preparation stage, the implementation stage, program preparation, program implementation, and reporting. At the preparatory stage, the team conducted a location survey and recruited participants for the service, and at the implementation stage there were several stages carried out by the team including: problem identification and needs analysis. The results of program implementation showed that the results of an internal meeting held by Ilomata KKNT students and the head of Ilomata Village had concluded several problems that would become priority work for students in Ilomata Village, including: 1) the problem of stunting; 2) Identity of UMKM in Ilomata Village; 3) Awareness of loose animal breeders. Each of these problems has been carried out by UNG KKNT students well through the stages of socialization and counseling, labeling of UMKM identities, as well as installing billboards related to regulations for loose animal breeders. The conclusion from this implementation is that every activity carried out is inseparable from the role of the Ilomata community, village government, and Bilato sub-district government in solving every problem faced by Ilomata village.